Determining the Sustainability of Small and Medium Enterprises (SMEs): Application of Information Technology, Innovation and Collaboration - Sjarifudin, Didin; Hendayana, Yayan; Istianingsih, Istianingsih (Dinasti Publisher, 2024)
The objective of this composition is to establish a hypothesis concerning the relationship between variables, which may subsequently be employed for subsequent research within the domain of marketing management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and the journal Sinta. The findings of this study indicate that: 1) The utilization of information technology has a significant impact on the long-term viability of small and medium enterprises; 2) Innovation plays a crucial role in shaping the sustainability of small and medium enterprises; and 3) Collaboration exerts a notable influence on the sustainability of small and medium enterprises. The limitations of the data used in this research make the results less than optimal. This study holds significance for small and medium enterprises as it examines the potential impact of incorporating information technology, innovation, and cooperation on the long-term viability of such businesses.